Comparison of the national AML/CTF laws of the Republic of Latvia and the United Kingdom - Šubņikovs, Konstantins (Riga Graduate School of Law, 2023)
The purpose of this thesis is to compare and find the core differences in the national anti-money laundering and counter terrorism financing legal frameworks of the Republic of Latvia and the United Kingdom using the qualitative comparative interdisciplinary analysis. In order to identify the differences, an analysis of the legislations of both countries has been conducted with the particular emphasis being made on the legal framework, as well as the national peculiarities of legal and political spirits of both states. Particular attention paid to the event of Brexit and its influence on the legal framework of anti-money laundering and counter terrorism financing laws of the United Kingdom. Furthermore, in order to examine the technical differences in the legislation – an in-depth comparison of the ultimate beneficial owner and politically exposed person concepts is conducted with the emphasis being made on the definitions and identification procedures provided in the anti-money laundering and counter terrorism financing laws of the Republic of Latvia and the United Kingdom. In the course of the study, author reaches the conclusion identifying the core differences between the national anti-money laundering and counter terrorism financing legal frameworks of the Republic of Latvia and the United Kingdom, as well as between the concepts of ultimate beneficial owner and politically exposed person under the national laws of the two countries.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Anti-money laundering; Financial crimes; The United Kingdom; Latvia